Religion-State Relation Within the Suryalaya Qadiriyah Naqsyabandiyah Tariqa - Salahudin, Asep; Santoso, Try Riduwan; Hj Abd Karim, Norhayati binti; Hilmi, Akhmad Robittul (Pascasarjana IAIN Pontianak, 2023)
The assumption that a tariqa group opposes worldly attainment and power is incorrect; their engagement in practical politics stems from a moral duty to uphold the state’s unity and integrity. This article delves into the political communication established by a Sufi figure, Abah Anom, aiming to reinforce the teachings of the tariqa and its relevance to religion and the state. Employing a descriptive qualitative approach through literature review, this research obtained data from various documents such as lecture texts, announcements, and photographs. The findings reveal two strategies employed by Abah Anom to reinforce the relations between religion and the state. First, a focus on spiritual growth, emphasizing practice and religious knowledge as guiding principles. Second, the maintenance of relations with state leaders, fostering legitimacy as responsible citizens. This study concludes that the relations between religion and the state that constitute part of the teachings of the Qodiriyah Naqsabandiyah tariqa (TQN)serve as a means to advocate and position itself within Muslim communities and government, aligning with both religion and state objectives. Furthermore, it suggests that the roles of the kyai extend beyond a broker of culture; the kyai also plays the role of a broker of politics to preserve harmony among religious groups and uphold the state’s unity and integrity.